Pain Management Practices, Novel Therapies and Bioactives - Yashasvi Waisundara, Viduranga; Banjari, Ines; Balkić, Jelena (IntechOpen, 2021)
Pain is a health issue that warrants significant attention and has an immense impact on global healthcare systems. This book focuses on pain, particularly on its management, by providing fresh perspectives and novel insights, while at the same time examining related topics that have often been overlooked. Given that there is no permanent cure for pain, the book primarily serves as an update to the existing knowledge. Topics covered include the biochemical pathways of pain as well as pharmaceutical and clinical management of pain to ensure health and wellbeing.